Structural Characterization of Fibrils from Recombinant Human Islet Amyloid Polypeptide by Solid-State NMR: The Central FGAILS Segment Is Part of the β-Sheet Core. - Franziska Weirich; Lothar Gremer; Ewa A Mirecka; Stephanie Schiefer; Wolfgang Hoyer; Henrike Heise (PLoS ONE, 2016)
Amyloid deposits formed from islet amyloid polypeptide (IAPP) are a hallmark of type 2 diabetes mellitus and are known to be cytotoxic to pancreatic β-cells. The molecular structure of the fibrillar form of IAPP is subject of intense research, and to date, different models exist. We present results of solid-state NMR experiments on fibrils of recombinantly expressed and uniformly 13C, 15N-labeled human IAPP in the non-amidated, free acid form. Complete sequential resonance assignments and resulting constraints on secondary structure are shown. A single set of chemical shifts is found for most residues, which is indicative of a high degree of homogeneity. The core region comprises three to four β-sheets. We find that the central 23-FGAILS-28 segment, which is of critical importance for amyloid formation, is part of the core region and forms a β-strand in our sample preparation. The eight N-terminal amino acid residues of IAPP, forming a ring-like structure due to a disulfide bridge between residues C2 and C7, appear to be well defined but with an increased degree of flexibility. This study supports the elucidation of the structural basis of IAPP amyloid formation and highlights the extent of amyloid fibril polymorphism.